Seasonal Dynamics and Predilection Sites of Ticks (Acari: Ixodidae) Feeding on Cows in the Western Parts of the Djurdjura, Algeria - Bedouhene, Amina; Kelanemer, Rabah; Medrouh, Bachir; Kernif, Tahar; Saidi, Fairouz; Tail, Ghania; Ziam, Hocine (Frontiers in Tropical Diseases, 2022)
The present study aimed to determine the phenology and predilection sites of ticks infesting cattle in the western region of Djurdjura (North Algeria) from November 2018 and October 2020. Nineteen cattle farms located in thirteen localities within four provinces were visited monthly for two years. Among the 289 examined cattle, 64.36 ± 2.81% (n=189) were infested by ticks. Of the 10,243 collected ticks, the most abundant tick species was Rhipicephalus bursa (31.57 ± 0.46%), followed by R. annulatus (31.26 ± 0.45%), Hyalomma marginatum (10.67 ± 0.30%), H. lusitanicum (7.02 ± 0.25%), H. excavatum (5.52±%0.22), H. scupense (4.27 ± 0.19%) and H. impeltatum (3.32 ± 0.17%). Ticks of the Hyalomma species were present throughout the year but in a limited number during the winter. H. scupense and H. impletatum showed similar activity from March to October and peaked in April and July, respectively (P<0.001). H. lusitanicum and H. excavatum were active from April to November and both peaked in September and October respectively. Rhipicephalus bursa was collected from April to August and R. annulatus from July to October. R. turanicus was active between April and June. Hyalomma genus had an affinity of attachment for the inguinal region (P<0.001). All parasitic stages of R. annulatus had an affinity for the necks (P<0.001). Nymphs of R. bursa prefer the neck (P<0.001), the adults attach to the perennial and inguinal regions (P<0.001). R. turanicus attach to the ears (P<0.001). As far as we know, this is the first study on the phenology and predilection sites of cattle ticks in the west region of Djurdjura in Algeria.